ESCAVANDO O CHÃO DA FUTILIDADE: COLUNAS SOCIAIS, FONTES PARA O ESTUDO DE ELITES LOCAIS (Revista de História Regional, 2007)
In this article are developed some methodological questions related to the uses of press as document In historical investigations. Specific attention is given to the characteristics of gossips columns. Some of its potentialities In the study of local reference groups, elites and socio-professional categories are dis-cussed.